رؤيــــــــة تحليلية لمستقبل قطاع النقل كأحد أهداف التنمية المستدامة في الجزائر (من خلال تحليل بعض الدراسات الميدانية) - قيطون محمد; محسن زوبيدة (جامعة الوادي University of Eloued, 2024)
تهدف هذه الدراسة تسليط الضوء على أهم الاستراتيجيات والنتائج التي مست قطاع النقل الحضري في الجزائر، مع الوقوف على مدى تحقيقه للتنمية المستدامة، من خلال تطوير خيارات النقل المستدامة التي ستساعد على تقليل الأضرار البيئية، حيث تشمل أهداف التنمية المستدامة خفض انبعاثات التلوث الناتجة عن قطاع النقل إلى النصف بحلول عام 2030، والى صفر(00) انبعاث بحلول عام 2050. ومن خلال تحليل أهم الدراسات الدولية التي تناولت كيفية وضع أسس الانتقال السليم نحو تجسيد النقل المستدام حول العالم، وإسقاطها على حالة الجزائر كتجربة فتية تنتظر النتائج مستقبلا، من هنا، توصلنا من خلال هذه الدراسة إلى أنه من اجل تجسيد مفهوم النقل المستدام، لابد يقوم ها الأخير على التخطيط المتكامل في الميدان الاقتصادي والثقافي والتقني والبيئي على حد سواء، هذا من خلال الإدارة الحكيمة لقطاع النقل واعتماد موارد نظيفة للوقود وتحسين البنية التحتية والخدمات المقدمة للمتنقلين، من اجل الحفاظ صحة الإنسان وسلامة البيئية والمحيط، والحفاظ على موارد الأجيال القادمة، وبالتالي الوصول إلى تحقيق تنمية مستدامة لقطاع النقل في الجزائر. This study aims to shed light on the most important strategies and results that have affected the urban transport sector in Algeria, while standing on the extent to which it has achieved sustainable development, through the development of sustainable transport options that will help reduce environmental damage, as the sustainable development goals include reducing pollution emissions from the transport sector to Half by 2030, and zero (00) emissions by 2050. And by analyzing the most important international studies that dealt with how to be the transition towards the sustainable transport in the world, and projecting them on case of Algeria as experiment awaiting results in the future, as a conclusion that in order to embody the concept of sustainable transport, it must be based on integrated planning in the field Economic, cultural, technical and environmental sectors, through the wise governance of the transport sector, the adoption of clean fuel resources, the improvement of infrastructure and services provided to commuters, in order to preserve human health and environmental safety, and to preserve the resources of future generations, and thus reach the realization of the concept of sustainable development.
A prospective vision for the future of sustainable transport as one of the sustainable development goals in Algeria (Through analyzing some field studies)
Keywords: نقل حضري; تلوث; تنمية مستدامة; جزائر